SH waves diffusion in fluid-saturated medium - Abd. Aziz, Zainal (Science Publications, 2010)
Problem statement:Characteristics of the seismic waves have been studied mainly the amplitudes, attenuation, frequency, porosity and the velocity of the waves. In this study, the SH-waves were studied for the diffusion which was related to the diffraction of SH-waves in the saturated medium. Approach: The elastic wave equation was being used to show the SH-waves. A comparison was made of the propagating SH-waves in the fluid-saturated mediums that were categorized into two distinct groups: Insoluble and soluble mediums. Results: The discussions on fluid density in the mediums showed that high density fluid promotes diffusive characteristic while low density fluid endorses non diffusive SH-wave. However, the diffraction had induced significant shock wave in the medium saturated with low density fluid. Conclusion: These results indicated that the linear seismic waves are able to transform into nonlinear waves.